Smartphone-based imaging colorimetric assay for monitoring the quality of curcumin in turmeric powder - Jongjit Jantra; Siriwan Teepoo; Suchera Thananimit (My University, 2024)
This research developed a colorimetric assay for semi-quantitative curcumin detection. The screening test was performed using a ferric chloride to form a brownish color which was further used to evaluate the amount of curcumin in the turmeric powder samples. The quantitative assay was performed based on the color intensity of the curcumin target using a smartphone digital image colorimetry with a developed lightbox constructed with a white light-emitting diodes (LED) light source as the measurement device. Images in red, green, and blue (RGB) color were processed to obtain relevant colors from the image and the color values were used to analyze curcumin concentrations. The intensity of the ΔB was correlated to the concentration of curcumin with high sensitivity. The method showed a linear range between 0.25 and 5 mg L−1 with the LOD and LOQ of 0.12 and 0.41 mg L−1, respectively. Sample analysis was carried out in turmeric powders. Curcumin in turmeric powder samples was simply extracted using acetonitrile followed by dilution 100 times for sample preparation. The accuracy was tested by spiking 0.25, 1.00, and 4.00 mg L−1 of standard curcumin into the turmeric sample solution. The average percentage recoveries were acceptable in all samples (90–104%). The method was validated by comparing the results obtained from the proposed method and high-performance liquid chromatography (HPLC). There was no statistically significant difference between the two methods (P = 0.05).
Keywords: Colorimetry; RGB color model; Quantitative Analysis; Dilution; Curcumin's Biomedical Applications